2019
DOI: 10.1016/j.cegh.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trend of suicide in center of Iran from 2012 to 2016

Abstract: Suicide is a conscious act in which the individual deliberately commit and unusual act with the intention of self-harm. The present study aims to examine some epidemiological factors affecting attempted and completed suicide rate during 2012-2016 in NajafAbad, a city in Isfahan province. Methods: This is a cross-sectional study. The subjects are 2138 cases involved in suicide attempt during 2012-2016 that gone to Montazeri and Al-Zahra hospital. Chi-square, logistic regression and Cochran-Armitage test was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…Various studies reported a direct relationship between the marital status of females and suicide attempts (20,36). According to the results, people with a diploma and school students had the highest rate of suicide attempts, respectively, which is consistent with other studies (2,22,37). This finding can be attributed to the higher frequency of high school diploma in Iranian society.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…Various studies reported a direct relationship between the marital status of females and suicide attempts (20,36). According to the results, people with a diploma and school students had the highest rate of suicide attempts, respectively, which is consistent with other studies (2,22,37). This finding can be attributed to the higher frequency of high school diploma in Iranian society.…”
supporting
confidence: 85%
“…Based on the results, drug intoxication is the most common method of suicide attempt (83.3% of females and 66.9% of males), which is consistent with various Iranian studies (22,24,36,37). It may be due to easy access to drugs in Iran.…”
supporting
confidence: 83%
See 3 more Smart Citations